Contributions of Limb Joints to Energy Absorption during Landing in Cats - Xueqing Wu; Baoqing Pei; Yuyang Pei; Nan Wu; Kaiyuan Zhou; Yan Hao; Wei Wang (Applied Bionics and Biomechanics)
There is a high risk of serious injury to the lower limbs in a human drop landing. However, cats are able to jump from the same heights without any sign of injury, which is attributed to the excellent performance of their limbs in attenuating the impact forces. The bionic study of the falling cat landing may therefore contribute to improve the landing-shock absorbing ability of lower limbs in humans. However, the contributions of cat limb joints to energy absorption remain unknown. Accordingly, a motion capture system and plantar pressure measurement platform were used to measure the joint angles and vertical ground reaction forces of jumping cats, respectively. Based on the inverse dynamics, the joint angular velocities, moments, powers, and work from different landing heights were calculated to expound the synergistic mechanism and the dominant muscle groups of cat limb joints. The results show that the buffering durations of the forelimbs exhibit no significant difference with increasing height while the hindlimbs play a greater role than the forelimbs in absorbing energy when jumping from a higher platform. Furthermore, the joint angles and angular velocities exhibit similar variations, indicating that a generalized motor program can be adopted to activate limb joints for different landing heights. Additionally, the elbow and hip are recognized as major contributors to energy absorption during landing. This experimental study can accordingly provide biological inspiration for new approaches to prevent human lower limb injuries.